AB1130 LOCALIZATION OF MRI INFLAMMATORY LESIONS OF THE HAND IN SCLERODERMA AND RHEUMATOID ARTHRITIS - COMPARATIVE STUDY. (2nd June 2020) - Stamenković, B.; Stankovic, A.; Stojanović, S.; Živković, V.; Djordjevic, D.; Nedovic, J.
Abstract : Background: Inflammatory lesions of hand are frquent clinical feature in rheumatoid artritis (RA), with lower frequency in pts with systemic sclerosis (SSc), also. MR is useful method for detecting and quantification of inflammatory lesion of the hand (bone oedema, erosions, synovitis) in RA and SSc. Objectives: The aim of the study was to compare MR hand feature in SSc (experimental) and RA (control group) and to detect the localisation of the highest OMERACT RAMRISinflammatory score on the hand in pts with SSc and RA Methods: 110 pts with SSc and 60 with RA were investigated (mean age 53y). All the pts underwenr clinical examination, X ray and MR on the dominant hand and wrist. Contrast enhanced low field MRI of the wrist and MCP2-5 joints was performend to all the pts. MRI inflammatory changes (bone oedema, erosions, synovitis)were assessed and scored by OMERACT RAMRIS scoring system. Results: Clinical examination confirmed synovitis in 17.1%, and 78% of patients with SSc using MR I (p <0.001). In the SSc group, erosions (by MR method) was confirmed in 52 (63.4%), by radiography in 22 pts (27.5%), which is a significantly lower percentage (p <0.001). In the control RA group, erosion was confirmed in 34 (97.1%) by MR method, and by radiography in 6 (17.1%), which is a statistically significant difference (p <0.001). Mean values of total MR score of synovitis (2.69 ± 2.29: 4.37 ± 1.31), oedema (6.58 ± 10.89: 20.57 ± 10.23) and erosion (6.84 ± 7, 43: 18.60 ± 5.01) on the wrist of the dominant hand were significantly higher in subjects with control RA than in those in the experimental SSc (p < 0.001). Mean values of total MR score of synovitis (3.15 ± 2.95: 5.26 ± 2.09), oedema (3.99 ± 9.82: 10, 51 ± 7.90) and erosion (4, 04 ± 4.76: 9.69 ± 4.27) on the MCP joints of the dominant hand were significantly higher in the control RA subjects (p <0.001).The highest OMERACR RAMRIS synovitis score was on distal radioulnar (DRU joint) of hand in SSc and also In RA pts. The highest erosion score was found on capitate bone in SSc, but in lunate bone in RA pts. The highest bone oedema score was also found on capitate bone in SSc, but in lunate bone in RA pts. According to the MCP joints, the highest synovitis score was found on the second finger in SSc and RA, highest erosion score also on the second finger in SSc, but on the third finger in RA; The highest bone oedema score was found on the third finger in SSc, and olso on the third and fifth finger in RA pts Conclusion: MR inflammatory lesions in SSc are less frequent compared to that in RA but still in significant percentage, confirming the need for early detection and aggressive treatment of both, RA and SSc patients with joint involvement References: [1]Avouac J, Walker UA, Hachulla E, Riemekasten G, Cuomo G, Carreira PE, et al. Joint and tendon involvement predict disease progression in systemic sclerosis: a EUSTAR prospective study. Annals of the rheumatic diseases. 2016;75(1):103–9. [2]Abdel-Magied RA, Lotfi A, AbdelGawad EA. Magnetic resonance imaging versus musculoskeletal ultrasonography in detecting inflammatory arthropathy in systemic sclerosis patients with hand arthralgia. Rheumatology international. 2013;33(8):1961–6.doi:10.1007/s00296-013-2665-8. Disclosure of Interests: None declared